2022
DOI: 10.1177/02698811221108956
|View full text |Cite
|
Sign up to set email alerts
|

The CannTeen Study: Cannabis use disorder, depression, anxiety, and psychotic-like symptoms in adolescent and adult cannabis users and age-matched controls

Abstract: Background: Adolescence is characterised by psychological and neural development. Cannabis harms may be accentuated during adolescence. We hypothesised that adolescents would be more vulnerable to the associations between cannabis use and mental health and addiction problems than adults. Method: As part of the ‘CannTeen’ study, we conducted a cross-sectional analysis. There were 274 participants: split into groups of adolescent users ( n = 76; 16–17 years old) and controls ( n = 63), and adult users ( n = 71; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Interestingly, a separate analysis of cross-sectional 'CannTeen' data has found AdolescentsWUC to have greater odds of having severe CUD than AdultsWUC, measured by DSM-5 symptoms (Lawn et al, 2022). Our findings of age-differences in cannabis demand suggest that adolescents may be in a riskier category who are less sensitive to price and have greater cannabis consumption when it is free.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Interestingly, a separate analysis of cross-sectional 'CannTeen' data has found AdolescentsWUC to have greater odds of having severe CUD than AdultsWUC, measured by DSM-5 symptoms (Lawn et al, 2022). Our findings of age-differences in cannabis demand suggest that adolescents may be in a riskier category who are less sensitive to price and have greater cannabis consumption when it is free.…”
Section: Discussionmentioning
confidence: 61%
“…This is an analysis of cross-sectional data from the baseline session of the longitudinal CannTeen study (Lawn et al, 2022). The study protocol describes aims, participants, power analysis, data collection procedures, tasks and timelines (Lawn et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Readers are directed to the full study protocol (Lawn et al, 2019) for further specification of aims, data collection procedures, tasks, and power calculations for the full project. Other recent manuscripts report the full study and have focussed on cognitive effects and clinical symptoms in this cohort (Will Lawn et al, 2022; W Lawn et al, 2022). Participants attended five behavioural sessions, one every three months, over the course of one year.…”
Section: Methodsmentioning
confidence: 99%
“…Lawn et al (2022) reported findings from the CannTeen Study, particularly cannabis use disorder, depression, anxiety and psychotic-like symptoms in adolescent and adult cannabis users and age-matched controls. Harms from cannabis may be greater in adolescence due to effects on psychological and brain development.…”
mentioning
confidence: 99%
“…No dose of cannabidiol examined induced feelings of intoxication or impaired cognition and interestingly the plasma measures of can nabidiol persisted longer than expected. Lawn et al (2022) reported findings from the CannTeen Study, particularly cannabis use disorder, depression, anxiety and psychoticlike symptoms in adolescent and adult cannabis users and agematched controls. Harms from cannabis may be greater in adolescence due to effects on psychological and brain develop ment.…”
mentioning
confidence: 99%